Highly active MgO catalysts for hydrogenation of levulinic acid to γ-valerolactone using formic acid as the hydrogen source - Sultana, Asima; Lomate, Samadhan; Fujitani, Tadahiro (Frontiers in Energy Research, 2023)
This study presents the first report on vapor phase levulinic acid (LA) hydrogenation to γ-valerolactone (GVL) using formic acid (FA) in an aqueous medium over unsupported simple oxide catalysts with varying acid-base properties. Among the different oxides tested MgO catalyst is found to be highly active. Among the MgO prepared by different methods and commercially obtained, the MgO-UBE showed 100% LA conversion and 100% selectivity to GVL at 270 °C. The MgO-UBE catalyst favorably allowed the production of γ-valerolactone in the presence of 50 wt% water relative to the amount of a mixture of levulinic acid and formic acid. Based on the catalytic activity and characterization results, it was concluded that the presence of Mg(OH)2 and a higher number of Lewis acid-base pair sites, Mg2+LCO2-LC are needed to achieve high levulinic acid conversion and GVL selectivity. Mg